Computer tomographic semiotics of retroperitoneal leiomyosarcoma arising from the muscular wall of the splenic vein: a case report - I. D. Lagkueva; V. A. Rebrikova; E. V. Egorova; N. L. Sergeev; P. M. Kotlyarov; O. P. Bliznyukov (Сибирский онкологический журнал)
Background. Diagnostic imaging of retroperitoneal neoplasms that arise within the retroperitoneal space but outside the major organs in this space is challenging due to the presence of large spaces filled with fatty tissue that allows the tumor to develop asymptomatically for a long time. In addition, these tumors are rare, and radiological semiotics and clinical manifestations can be nonspecific.Case presentation. We present the rare clinical case of a 53-year-old patient with a large retroperitoneal mass detected by contrast-enhanced computed tomography. Additional imaging diagnostic procedures as well as histological findings helped to make a definitive diagnosis: extraorganic retroperitoneal leiomyosarcoma arising from the muscular wall of the splenic vein.Conclusion. The retrospective analysis of CT data showed that the tumor-induced marginal defect in the contrasted splenic vein may indicate the tumor arising from the muscular wall of the vessel. The final diagnosis was made on the basis of a morphological study.